On identity for eigenvalues of second order differential operator equation - Bayramov, Azad; Oer, Zerrin; Baykal, Oya (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
In this study we investigate the spectrum and regularized trace of the second order differential operator equation with periodic boundary conditions. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Hilbert space; Self-adjoint operator; Kernel operator; Spectrum; Regularized trace; Computer Science; Mathematics